2017
DOI: 10.1111/jcpp.12749
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety symptoms and children's eye gaze during fear learning

Abstract: Anxiety symptoms in children relate to face-viewing strategies deployed in the context of a fear learning experiment. This relationship may inform attempts to understand the relationship between pediatric anxiety symptoms and learning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 61 publications
2
26
0
Order By: Relevance
“…There are less empirical findings relating the effects of fear conditioning on gaze behavior. Michalska et al (2017) showed that children hold their gaze more often and longer toward the area of the eyes of a CS+ than a CS−. The authors used two neutral faces as conditioned stimuli (CS+ and CS−).…”
Section: Discussionmentioning
confidence: 99%
“…There are less empirical findings relating the effects of fear conditioning on gaze behavior. Michalska et al (2017) showed that children hold their gaze more often and longer toward the area of the eyes of a CS+ than a CS−. The authors used two neutral faces as conditioned stimuli (CS+ and CS−).…”
Section: Discussionmentioning
confidence: 99%
“…Total scores were calculated by summing all item-level scores. Total scores from each parent–youth dyad were averaged (Guyer et al ., 2008; Michalska et al ., 2017; Shechner et al ., 2017) to create a mean score reflecting current symptom severity for each participant.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, extant work demonstrates that the ability to manage emotion is needed to maintain healthy relationships (Blair & Raver, ) and foster social competence (Calkins, Gill, Johnson, & Smith, ). On the other hand, certain developmental disorders are marked by deficits in emotion reactivity and regulation, which influence the motivation and ability to respond to others’ needs (Michalska et al, ; Michalska, Zeffiro, & Decety, ). Failure to acquire the skills required to manage emotional responses may lead to difficulties in social interaction (Calkins, ; Cicchetti, Ackerman, & Izard, ; Rubin, Coplan, Fox, & Calkins, ).…”
Section: Emotion Reactivity and Regulationmentioning
confidence: 99%
“…On the other hand, certain developmental disorders are marked by deficits in emotion reactivity and regulation, which influence the motivation and ability to respond to others' needs (Michalska et al, 2017;Michalska, Zeffiro, & Decety, 2016). Failure to acquire the skills required to manage emotional responses may lead to difficulties in social interaction (Calkins, 1994;Cicchetti, Ackerman, & Izard, 1995;Rubin, Coplan, Fox, & Calkins, 1995).…”
Section: Introductionmentioning
confidence: 99%